Axial performance of GGBFS concrete filled steel tubes. (February 2020) - Ahmad, Subhan; Kumar, Ajay; Kumar, Kamal
Abstract: Fifteen circular concrete-filled-steel tubes (CFST) containing ground granulated blast furnace slag (GGBFS) concretes were tested in axial compression. CFST columns were casted with four concrete mixtures having 0, 15, 25 and 35% GGBFS replacement levels and two different length-to-diameter ratio of 2.87 and 4. Compressive strength for concrete mixtures was determined after 28, 56 and 90 days. Time-dependent compressive strengths of GGBFS concretes were also compared with those predicted by the equation of MC-10. Axial capacities of GGBFS concrete CFSTs were found to be more than those of control concrete CFSTs. Increase in axial capacity of CFSTs was proportional to the increase in compressive strength of concrete mixtures due to the inclusion of GGBFS. Stiffness of GGBFS concrete CFSTs were similar to those of control concrete CFSTs. Experimental axial capacities of CFST columns tested were also compared with the provisions of Architectural Institute of Japan (AIJ), ACI 318, Chinese code (DL/T) and EC 4. ACI 318 was found to be most over conservative followed by AIJ for the estimation of axial capacities of GGBFS concrete CFST columns. EC 4 and DL/T provisions provided accurate estimates of the axial capacities of GGBFS concrete CFST columns. Furthermore, embodied energy (EE) and cost of CFSTs with different concretes are also compared. EE and cost of CFST was reduced linearly with the increase in GGBFS content in concrete.